2020
DOI: 10.1016/j.earscirev.2020.103218
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical methods to infer landscape response to Quaternary climate change and land use in depositional archives: A review

Abstract: Understanding and quantifying the processes and geochemical cycles associated with catchment erosion, the development of soils and weathering horizons, and terrestrial habitat change beyond the scales of modern observations remain challenging. Such research, however, has become increasingly important to help predict future landscape change in light of increasing land use and rapid global warming. We herein review organic and inorganic geochemical tools applied to depositional archives to better understand vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 224 publications
(279 reference statements)
0
9
0
Order By: Relevance
“…Palaeo-sediment residence times are a measure of catchment erosion, which depends on catchment size and morphology, bedrock geology, chemical weathering, vegetation, and climate Francke et al, 2020a;Thollon et al, 2020). Of these factors, catchment size, morphology, and geology were effectively constant over the time interval investigated herein.…”
Section: Catchment Vegetation Cover and Catchment Erosionmentioning
confidence: 91%
See 3 more Smart Citations
“…Palaeo-sediment residence times are a measure of catchment erosion, which depends on catchment size and morphology, bedrock geology, chemical weathering, vegetation, and climate Francke et al, 2020a;Thollon et al, 2020). Of these factors, catchment size, morphology, and geology were effectively constant over the time interval investigated herein.…”
Section: Catchment Vegetation Cover and Catchment Erosionmentioning
confidence: 91%
“…However, there is little information on the fate of SOC during soil erosion, introducing large uncertainties into national carbon flux estimates, Earth System Models (ESM), and General Circulation Models (GCM, Doetterl et al, 2016;Lugato et al, 2018;Francke et al, 2020a). Reanalysis of national greenhouse gas emissions in Australia, for example, has suggested that not considering cropland soil erosion overestimated the nation's net carbon flux into the atmosphere by 40% (Chappell et al, 2015), explained by SOC lost by erosion and subsequently buried in sedimentary sinks rather than being re-oxidised (Chappell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, LD was considered to be a specific issue of some territories due to particular sequences of natural drivers (Francke et al, 2020;Larrey et al, 2020). LD is generally associated to biophysical conditions (soil characteristics, steep slopes, lack of vegetation cover, (e.g.…”
Section: Introductionmentioning
confidence: 99%